Digital Image Processing An Algorithmic Introduction - Burger, Wilhelm; Burge, Mark J. (Cham : Springer International Publishing : Imprint: Springer, 2022)
This modern, self-contained textbook provides an accessible introduction to the field from the perspective of a practicing programmer, supporting a detailed presentation of the fundamental concepts and techniques with practical exercises and fully worked out implementation examples. This much-anticipated 3rd edition of the definitive textbook on digital image processing has been completely revised and expanded with new content, improved illustrations and teaching material. Topics and features: Contains new chapters on fitting of geometric primitives, randomized feature detection (RANSAC), and maximally stable extremal regions (MSER) Includes exercises for most chapters and provides additional supplementary materials and software implementations at an associated website Uses ImageJ for all examples, a widely used open source imaging environment that can run on all major platforms Describes each solution in a stepwise manner in mathematical form, as abstract pseudocode algorithms, and as complete Java programs that can be easily ported to other programming languages Presents suggested outlines for a one- or two-semester course in the preface Advanced undergraduate and graduate students will find this comprehensive and example-rich textbook will serve as the ideal introduction to digital image processing. It will also prove invaluable to researchers and professionals seeking a practically focused self-study primer. Dr. Wilhelm Burger is an emeritus of the University of Applied Sciences Upper Austria at Hagenberg, where he served as Head of the Digital Media degree programs at the School of Informatics, Communications and Media. Dr. Mark J. Burge is the Senior Advisor for Artificial Intelligence at the Federal Bureau of Investigation, Washington, DC, USA. His other publications include the Handbook of Iris Recognition.
1. Digital Images -- 2. ImageJ -- 3. Histograms and Image Statistics -- 4. Point Operations -- 5. Filters -- 6. Edges and Contours -- 7. Corner Detection -- 8. Finding Simple Curves -- 9. Morphological Filters -- 10. Regions in Binary Images -- 11. Automatic Thresholding -- 12. Color Images -- 13. Color Quantization -- 14. Colorimetric Color Spaces -- 15. Filters for Color Images -- 16. Edge Detection in Color Images -- 17. Edge-Preserving Smoothing Filters -- 18. Introduction to Spectral Techniques -- 19. The Discrete Fourier Transform in 2D -- 20. Geometric Operations.
Keywords: Computer vision; Signal processing; Computational intelligence; Computer Vision; Digital and Analog Signal Processing; Computational Intelligence; Signal, Speech and Image Processing .